Home-Based Exercise, Health Education, and Dietary Control Improve Elderly Well-Being in Buriram, Thailand - Namvicha, Kittisak; Sujayanont, Patcharawan; Nithikathkul, Choosak (Edelweiss Applied Science and Technology, 2025)
Thailand has transitioned into an aging society, resulting in health challenges such as chronic diseases and malnutrition, which affect the quality of life of older adults. Therefore, promoting health through exercise programs, health education, and dietary control is crucial for enhancing the health status of older adults in communities. This quasi-experimental research aimed to investigate the effects of a home-based exercise program combined with health education and dietary control on older adults in Buriram Province. The sample comprised 194 older adults, selected through multi-stage sampling. Data were collected between April and November 2024 using a physical fitness assessment record, knowledge test, and quality-of-life questionnaire. The reliability coefficient was 0.72, and the content validity index (IOC) ranged from 0.60 to 1.00. The data were analyzed using an independent t-test. The experimental group exhibited statistically significant improvements (p < .05) in physical fitness indicators, such as arm curl strength, chair stand test, and back scratch test. These improvements persisted during the three-month follow-up period. Regarding health, nutrition, and exercise knowledge, the experimental group scored significantly higher than the control group. Additionally, the quality-of-life scores of the experimental group remained higher than those of the control group, both after the intervention and during the follow-up period. The home-based exercise program, combined with health education and dietary control, effectively enhanced the health and quality of life of older adults.